Mr. Putter & Tabby : Smell the roses - Rylant, Cynthia; Howard, Arthur (Boston : Houghton Mifflin Harcourt, 2015)
"Mr. Putter wants Mrs. Teaberry's birthday to be extra special this year. So how about a trip to the Conservatory to see the beautiful trees and plants and flowers? It will be heavenly. And it is! Mr. Putter and Tabby and Mrs. Teaberry and Zeke sniff the air. They smell the roses. They learn the plant facts. It's the perfect celebration... until Zeke finds the banana tree"--Dust jacket.
Booklist
Horn Book
School Library Journal
Booklist, August 2015
Horn Book, April 2016
School Library Journal, August 2015
Keywords: Birthdays -- Juvenile fiction; Cats -- Juvenile fiction; Conservatories -- Juvenile fiction; Dogs -- Juvenile fiction; Birthdays -- Fiction; Cats -- Fiction; Conservatories -- Fiction; Dogs -- Fiction; Birthdays -- Fiction; Cats -- Fiction; Conservatories -- Fiction; Dogs -- Fiction